Post-earthquake design restoration process for Our Lady of the Assumption Church in Dauis, Bohol - Miano, Pasquale; Vassallo, Candida Maria (2016)
The theme of the restoration of the Dauis Church of the Assumption of Our Lady in the island of Bohol is tackled on the basis of the interpretation of post-emergency design as a process. The 2013 earthquake created a violent rupture that caused extensive damage to the church and the loss of important reference point for the community. In this situation, the design must resolve the restoration of the Church while preserving the authenticity of Dauis and at the same time, take into account what has changed because of the disater. This requires a precise approach, under which eery architectural intervention must assess its consequences in relation to the needs of the Catholic community, the identity of the religious complex and the surrounding landscape. This approach gives the post-emergency restoration design its specific accentuations, in which it must not simply draw up a restoration plan, but activate an articulated design process. In particular, the role of the community is articulated because it is deeply rooted in the Catholic tradition and it was already involved in the post-emergency process through the construction of a temporary church. The theme of the restoration of the damaged church is articulated, because it is possible to insert architectural elements (through the contemporary visible traces) that require a critical and interpretive attitude. Finally, the established relationship between the site and the structure within the religious complex are articulated in which temporarily and destruction are recognized as historical layers and one cannot simply reconstruct to return the structure to its original configuration and meaning.
Keywords: Church buildings -- Panglao (Bohol); Church buildings -- Preservation and restoration; Dauis Church of the Assumption of Our Lady (Panglao, Bohol)